Attached once, attached forever: The persistent effects of concertaje in Ecuador - Alex Rivadeneira (Banco de México, 2024)
This paper studies the long-run effects of concertaje, a forced labor system from the Spanish colonial era in Ecuador that coerced indigenous workers in rural estates after indebting them. I collected and digitized historical tax records (1800) and connected them to contemporary ones (2010s) via surnames. Employing a TS2SLS approach, I find that a 10 percentage point (pp) increase in a surname's concertaje rate reduces the current formal income of (pseudo) descendants by 1.7%. On a regional scale, I establish a causal relationship by leveraging variations in concertaje intensity due to differences in crop labor requirements. IV estimates show that a 10 pp rise in a district's concertaje rate increases contemporary poverty by 4.2 pp. As channels of persistence, I show that concertaje historically led to lower education levels, reduced public goods provision, increased agricultural employment, and inequality. Concertaje also limited mobility, although its effect on immigrants is milder, suggesting migration acted as a mitigation channel.
Keywords: N36; O10; O43; J62; 330; Institutions; Persistence; Forced Labor; Intergenerational Mobility; Ecuador